Pengaruh Citra Merek, Persepsi Harga, Dan Kualitas Produk Terhadap Keputusan Pembelian Melalui Peran Minat Beli Pada Produk Sabun Cuci Muka Garnier Men - Muharam, Indra Fahreza; Oswari, Teddy (ProBisnis : Jurnal Manajemen, 2025)
Generally, teenagers and adults who do activities outside the home must first use face wash in the facial area to keep it clean and healthy. One of the face wash brands that is currently in demand by the public is Garnier Men products. This study aims to determine and analyse the direct and indirect effects of brand image, perceived price, and product quality on purchasing decisions with purchase intention as an intervening variable in Garnier Men face wash products. This research method uses quantitative primary data. The sampling method used in this study was non-probability sampling with purposive sampling technique. Data collection using a questionnaire instrument with a total of 100 respondents. The analytical tool used is SmartPLS 4, the testing stages carried out are the research model test, measurement model (convergent validity test, discriminant validity, and reliability), structural model (R-Square test, Path coefficient, indirect effect, predictive relevance, and model fit). The results of this study indicate that brand image and product quality have a significant effect on purchase intention, price perception has an insignificant effect on purchase intention. Brand image, price perception, and product quality have an insignificant effect on purchasing decisions. Brand image and product quality have a significant effect on purchasing decisions with buying interest as an intervening variable. Price perception has an insignificant effect on purchasing decisions with buying interest as an intervening variable.